Slovak Republic--Joining the EU : a Development Policy Review. (World Bank country study., 2003)
The Slovak economy experienced in 2002 its best performance since recovering from the 1998 financial crisis. However, once recovery was under way, macroeconomic imbalance resurfaced and unemployment was at 18 per cent. This study presents an agenda for immediate and long-term policy action.